Pengaruh Realisasi Belanja Daerah Dan Upah Minimum Terhadap Tingkat Pengangguran Di Provinsi Lampung Dalam Perspektif Ekonomi Islam - Taufiqur Rahman; Rahma Apriani; Nurlaili Nurlaili; Supaijo Supaijo (Eqien - Jurnal Ekonomi dan Bisnis, 2023)
Abstract Unemployment is one of the problems that affect the welfare of society and the Indonesian economy. One of the employment problems is the imbalance between labor demand and labor supply. This study aims to analyze the effect of Realization of Regional Expenditure and Minimum Wage on the unemployment rate in Lampung Province from the perspective of Islamic economics partially and as a whole. This research is a quantitative study using multiple linear regression analysis techniques with Times series data and processed using the Eviews 10 program. The results of this study as a whole (test F) Regional Expenditure and Minimum Wage have a positive and significant effect on the unemployment rate in Lampung Province. Partially (T test) the Regional Expenditure variable has a negative and significant effect on the unemployment rate, the Minimum Wage variable has a positive and insignificant effect on the unemployment rate in Lampung Province. In this study, when viewed from an Islamic economic perspective, the goal of Islamic economics is to achieve a higher falah which is manifested through optimizing the benefit of the entire community through the realization of Regional Expenditures and the Lampung Province Minimum Wage in accordance with Allah's commands. Keywords: Regional spending, minimum wages, unemployment.